Implementation of Madrasah Policies in Realizing the Digital-Based Transformation of Islamic Religious Education Learning at MAN Tapanuli Tengah - Abdusima Nasution; Dimas Indianto S; Shobrun Jamil (Journal of General Education and Humanities, 2026)
This study aims to examine the transformation from conventional learning systems to digitally oriented learning systems in Islamic Religious Education (PAI) at State Islamic Senior High Schools (Madrasah Aliyah Negeri/MAN) in Tapanuli Tengah, Indonesia. The research focuses on the implementation of digital-based learning practices at MAN 1 Tapanuli Tengah and MAN 3 Tapanuli Tengah, highlighting how digital technologies support educational development and improve learning quality in the contemporary era. A qualitative research approach was employed using interviews, observations, and document analysis as data collection techniques. The collected data were analyzed using the interactive model of Miles and Huberman, comprising data reduction, data display, and conclusion drawing. The validity of the findings was ensured through source triangulation. The findings reveal that integrating digital technology into Islamic Religious Education has significantly transformed the learning process. Digital-based learning has enhanced students’ engagement, facilitated access to learning resources, and enabled the contextualization of learning materials into real-life situations. Furthermore, the use of digital platforms and educational technologies has created a more interactive and innovative learning environment, supporting both teachers and students in achieving educational objectives more effectively. The study implies that digital-based learning has become a strategic and sustainable approach for contemporary education. It offers educators opportunities to adapt instructional practices to technological advancements while maintaining educational values and improving learning outcomes. This research contributes to the growing body of knowledge on digital transformation in Islamic education and offers practical insights for policymakers and educators seeking to strengthen the implementation of digital learning in madrasah settings.